Revisão bibliográfica: os impactos causados no meio ambiente e saúde humana gerados pelo agrotóxico glifosato - OLIVEIRA, Henrique; CONCEIÇÃO, Joabe Vilela; GOMES, Mauro José; SOUZA, Michele Domingues Vieira de; VICENTE, Tatiane Santos (181, 2025)
O uso de agrotóxicos na agricultura tem se mostrado um fator essencial para o aumento da produtividade e segurança alimentar global. No entanto, os impactos econômicos desse uso são multifacetados e vão além dos benefícios imediatos à produção. Este trabalho tem como objetivo analisar os impactos do uso de agrotóxicos, considerando tanto os benefícios diretos, como o aumento da produtividade e o fortalecimento do setor agroindustrial, quanto os custos indiretos relacionados aos danos ambientais, à saúde pública e à resistência das pragas.

The use of pesticides in agriculture has proven to be an essential factor in increasing productivity and global food security. However, the economic impacts of this use are multifaceted and go beyond the immediate benefits to production. This study aims to analyze the economic impacts of pesticide use, considering both direct benefits, such as increased productivity and strengthening of the agro-industrial sector, and indirect costs related to environmental damage, public health, and pest resistance. The methodology adopted included a bibliographic review of academic studies on the use of pesticides, agricultural productivity, environmental costs, and health impacts, extracted from scientific databases such as Scielo and Google Scholar. Studies indicate that, although pesticides have allowed significant advances in food production, their excessive use has generated problems such as soil and water contamination, increased diseases related to exposure to chemical substances, and pest resistance, resulting in high costs for health systems and the economy. The study also addresses more sustainable alternatives, such as organic farming and biological pest control, which may represent viable solutions to reduce negative impacts and promote more balanced agriculture. It is concluded that, in order to ensure the sustainability of agriculture and mitigate the adverse effects of pesticide use, it is essential to adopt more sustainable agricultural practices, effective public policies and investments in technologies that minimize environmental and health impacts, promoting a balance between economic development and the preservation of natural resources.
Literature review: the impacts of glyphosate pesticides on the environment and human health
Keywords: Saúde pública; Meio ambiente; Agronomia; Ambiente e Saúde